Strong and tough metal/ceramic micro-laminates. (1st February 2018) - Ferraro, Claudio; Meille, Sylvain; Réthoré, Julien; Ni, Na; Chevalier, Jerome; Saiz, Eduardo
Abstract: There is a growing interest in the development of composites with complex structures designed to generate enhanced mechanical properties. The challenge is how to implement these structures in practical materials with the required degree of control. Here we show how freeze casting of ceramic preforms combined with metal infiltration can be used to fabricate Al2 O3 /Al-4wt% Mg micro-laminated composites. By manipulating the solid content of the suspension and the morphology of the ceramic particles (from platelets to round particles) it is possible to access a range of structures with layer thickness varying between 1 and 30 μm and metallic contents between 66 and 86 vol%. The mechanical response of the materials is characterized by combining bending tests with observation of crack propagation in two and three dimensions using different imaging techniques. These composites are able to combine high strength and toughness. They exhibit a rising R-curve behaviour although different structures generate different toughening mechanisms. Composites fabricated with Al2 O3 particles exhibit the highest fracture resistance approaching 60 MPa m 1/2, while laminates prepared from Al2 O3 platelets exhibit higher strengths (above 700 MPa) while retaining fracture resistance up to ∼40 MPa m 1/2 . The results provide new insights on the effect of structure on the mechanical properties in metal-ceramic composites as well as on the design of appropriate testing procedures. Graphical abstract: Image